3 D Ordered Macroporous Alumina–Carbon Nanocomposite Supported Platinum Nanoparticles as Effective and Reusable Catalysts for Asymmetric Hydrogenation. Issue 3 (28th December 2016) - Yang, Ting; Lou, Lan‐Lan; Yu, Wenjun; Feng, Yajun; Li, Hao; Yu, Kai; Liu, Shuangxi
Abstract: The three‐dimensionally ordered macroporous alumina‐carbon composite materials were firstly prepared through a surfactant‐assisted colloidal crystal template method and applied to support Pt nanoparticles. The results of SEM, XRD, TEM, and N2 sorption analyses revealed that these composite materials possessed highly ordered macroporous structures with meso‐ and micropores within the skeletons of macropores and that the Pt nanoparticles were well dispersed on these materials with a very narrow size distribution. These prepared Pt nanocatalysts were evaluated in the asymmetric hydrogenation of ethyl pyruvate after chiral modification with cinchonidine. Excellent catalytic activity and enantioselectivity were achieved. More importantly, these catalysts exhibited extraordinary stability and reusability during the reaction and could be reused at least 26 times without significant loss in catalytic activity and enantioselectivity. Abstract : Porous but extraordinarily durable : 3 D ordered macroporous alumina–carbon composite supported Pt nanocatalysts are applied in the asymmetric hydrogenation of ethyl pyruvate. They exhibit high catalytic activity and extraordinary durability.